Effects of Implantable Collamer Lens V4c Placement on Iridocorneal Angle Measurements by Fourier-Domain Optical Coherence Tomography - Fernández-Vigo, José Ignacio; Macarro-Merino, Ana; Fernández-Vigo, Cristina; Fernández-Vigo, José Ángel; Martínez-de-la-Casa, José María; Fernández-Pérez, Cristina; García-Feijóo, Julián (American journal of ophthalmology, 2016)
To assess by Fourier-domain optical coherence tomography (FDOCT) changes produced in iridocorneal angle measurements in patients undergoing Visian Implantable Collamer Lens (ICL) V4c (STAAR Surgical AG) placement. Prospective interventional case series. In 50 eyes of 25 myopic subjects consecutively scheduled for ICL implant, FDOCT (RTVue; Optovue Inc) iridocorneal angle measurements were made before and 1 and 3 months after surgery. Trabecular-iris angle (TIA) and angle opening distance 500 μm anterior to the scleral spur (AOD500) were compared among the quadrants nasal, temporal, and inferior, and correlations with ocular variables including lens vault were examined. Preoperative TIA was 48.7 ± 8.7, 48.2 ± 8.7, and 48.7 ± 9.3 degrees for the nasal, temporal, and inferior quadrants, with no differences (P = 1.000). Following ICL implant, corresponding values fell to 31.2 ± 11.5, 30.0 ± 10.7, and 29.7 ± 8.1 degrees at 1 month postsurgery, indicating angle narrowing of 34%–42%, and to 30.6 ± 12.3, 30.1 ± 11.9, and 29.8 ± 12.3 degrees, respectively, at 3 months postsurgery. Angle measurements failed to vary between 1 month and 3 months postsurgery (P = .481). In 8 eyes, iridotrabecular contact attributable to surgery was observed. One month after surgery, vault measurements correlated with TIA (R = −.309; P = .048). Six variables were identified as predictors of TIA at 1 month postsurgery (R2 = .907). Although considerable angle narrowing was detected 1 month after ICL V4c implant, this narrowing remained stable at 3 months postsurgery. Factors predictive of TIA could serve to identify suitable candidates for ICL placement.